PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SANSYU PRECISION BATAM - Mestika K Malau; Wasiman (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Performance is the result of individual work in terms of type and quantity, which is obtained from time to time and performs tasks according to the specifications set by the company. The success of the company can be seen from the good work. This research was conducted at PT Sansyu Precision Batam. The aim in this lesson is to show that the influence of work discipline and work environment on employee performance. The technique in using samples is done with probability with simple random sampling. The technique in collecting data uses quantitative techniques with the distribution of questionnaires as many as 115 which contain statements to interpret each of the contents of the thinking of employees of the work discipline system and the work environment that has been established at work. Researchers used the Statistical Application and Service Solution (SPSS) version 26 application in testing hypotheses. The results of the data obtained are: (1) work discipline partially has a significant effect on employee performance; (2) the work environment partially has a significant effect on employee performance; (3) work discipline and work environment simultaneously have a significant effect on employee performance.